Teacher’s Translanguaging Practices in EFL Classroom Interaction: A Case Study at SMP Negeri 1 Percut Sei Tuan - Nazwa Nur Rahmi; Nia Kristin Sianturi; Jemima Indah Andayani; Alfira Khairunnisa Br Nadapdap (CV Edu Tech Jaya, 2026)
This study aims to examine how translanguaging is practiced by the teacher and to explain the reasons for its use in EFL classroom interaction. The research applied a descriptive qualitative method, focusing on a teacher and approximately 24 students in class VII-3 at SMP Negeri 1 Percut Sei Tuan. Data were collected through classroom observation, audio recording, documentation, and interview, then analyzed using data condensation, data display, and conclusion drawing. The findings reveal that the teacher practices two major types of translanguaging: translanguaging shifts and instructional scaffolding. Translanguaging shifts are used in short utterances for giving instructions and feedback, while instructional scaffolding is applied in detailed explanations of grammar and text content. Furthermore, these practices are driven by several factors: the need to optimize communicative resources, the effort to connect with students' prior knowledge, the necessity to adapt to the classroom situation (flow of interaction), and the requirement for effective classroom control. Although these strategies facilitate comprehension, the interaction remains teacher-centered with limited student participation.